FLORA PANDAN KAWASAN SEMENDE, MUARA ENIM, SUMATERA SELATAN - Keim, Ary Prihardhyanto (Indonesian Journal of Biotechnology and Biodiversity, 2017)
AbstractEleven species of Pandanaceae are recorded from the vicinity of Semende, Muara Enim, South Sumatra, in which six species belong to the genus Freycinetia (F. insignis, F. rigidifolia, F. sumatrana, F. cf. angustifolia, F. cf. kamiana, and F. cf. scandens), two species are Pandanus (P. amaryllifolius and P. furcatus), and three species are Benstonea (B. korthalsii, B. cf. atrocarpa, and BenstoneP. a sp. ). One undescribed taxon identified here as Benstonea sp. probably represents a new species. Keywords : pandan, pandanaceae, sumatra AbstrakDi seluruh kawasan Semende, Muara Enim, Sumatra Selatan terekam sebelas jenis tumbuhan yang termasuk Pandanaceae; enam jenis termasuk marga Freycinetia (F. insignis, F. rigidifolia, F. sumatrana, F. cf. angustifolia, F. cf. kamiana, dan F. cf. scandens), dua termasuk marga Pandanus (P. amaryllifolius dan P. furcatus), serta tigatermasuk marga Benstonea (B. korthalsii, B. cf. atrocarpa, dan Benstonea sp. ). Takson Benstonea sp. diduga merupakan jenis baru Kata kunci : pandan, pandanaceae, sumatra